Industrial Internet in sustainable value creation of companies - Oja, Sampsa (My University, 2019)
As we are heading towards a more digitalized world, an increasing amount of opportunities lies ahead of us. The Industrial Internet is described to have a large impact for industries around the globe. This research focuses on exploring its effects on sustainable value creation of companies. While the subject has gained a lot of enthusiasm over the last couple of years, the overall sustainable value creation elements of the Industrial Internet have not been studied properly due to its novelty. Yet, understanding the effects on how and where the sustainable value comes from is crucial in understanding the opportunities and challenges better. The thesis is conducted by an extensive theoretical framework of the Industrial Internet phenomenon and its relevant sustainable value creation factors. The research is also done as a qualitative multiple case study to have a more in-depth understanding of the subject. The empirical findings represent five different top company personnel views, which have already implemented the Industrial Internet in their business processes. Different industry sectors were chosen to answer the research questions better and have a more comprehensive view of the issue. Furthermore, a theory-bound data analysis method is used to not only allow the comparisons to existing theory, but also gain the possibility to discover new information. The results show the quality of the data and the combination of data sources to be the crucial elements in extracting value from data. While the Industrial Internet has allowed the companies to create sustainable value by improving their existing internal services and processes through monitoring and optimizations, the overall measurable short-term value it has created has not been that impactful at this stage yet. Although, improving existing services could have an influence on preventing potential value loss for the companies. However, the results also indicate that by providing external services, such as data analysis for customers can bring extensive short-term value when executed properly. The findings also demonstrated the Industrial Internet to allow new business partners and opportunities to be created, which would not have been possible had the investments not been made. Those new opportunities can bring a competitive advantage to the company by providing differentiation and better service levels to the customers. While the results and implementations vary between the company, industry sector and expertise, the study can help companies to understand the opportunities and key factors behind the data better. The findings also help the companies that are discussing or in the process of implementing the Industrial Internet into their business processes to comprehend the crucial stages that need to be taken into consideration.
Keywords: Industrial Internet; IIoT; Data; Sustainable value creation; Business models; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Teknisen viestinnän maisteriohjelma|en=Master's Programme in Technical Communication|sv=Magisterprogrammet i teknisk kommunikation|